2021
DOI: 10.1158/1078-0432.ccr-20-2770
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Chimeric Antigen Receptor T Cells by ICOS-ImmunoPET

Abstract: In vivo Imaging of Activated Chimeric Antigen Receptor T Cells. Conflict-of-interest disclosures SSG is the founder and equity holder of CellSight Inc. that develops and translates strategies for imaging cell trafficking/transplantation. CLM holds several patent applications in the area of CAR T cell immunotherapy, is a founder of, holds equity in, and receives consulting fees from Lyell Immunopharma, has received consulting fees from NeoImmune Tech, Nektar Therapeutics and Apricity Health and royalties from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Based on this work, 89 Zr-DFO-ICOS mAb PET/CT has recently been used to visualize CAR-T cell activation. Significantly higher PET signal was detected in the bone marrow of mice with systemic B-cell lymphoma mice treated with CD19 CAR-T cells, which reflected their distribution and activation 139 .…”
Section: Endogenous Cell Imaging Methodsmentioning
confidence: 94%
“…Based on this work, 89 Zr-DFO-ICOS mAb PET/CT has recently been used to visualize CAR-T cell activation. Significantly higher PET signal was detected in the bone marrow of mice with systemic B-cell lymphoma mice treated with CD19 CAR-T cells, which reflected their distribution and activation 139 .…”
Section: Endogenous Cell Imaging Methodsmentioning
confidence: 94%
“…Due to high sensitivity of PET and SPECT, higher than that of MRI techniques, much lower concentrations of radiolabeled compounds can be used, making possible to avoid interference with cell function and viability (168,171). Using a 89 Zr-labeled anti-ICOS antibody, it was shown that PET can be a useful tool for in vivo tracking of CAR T cells in an orthotopic murine tumor model of lymphoma (172). One disadvantage of PET and SPECT being that they have a limited spatial resolution, combination with CT provides a first approach to surpass this limitation (173).…”
Section: In Vivo Monitoring Of Cellular Products and Treatment Efficacymentioning
confidence: 99%
“…HSV1-TK transduced lymphocytes and CD19 CAR T cells with truncated epithelial growth factor receptors have been used to provide a platform for both the imaging and tracking of cellular response, as well as the incorporation of suicide genes for safety in the setting of severe T cell immunologic response or graft vs. host disease [168,169]. Recently, a rodent model has adopted the use of 89 ZrDFO-Inducible T-Cell COStimulator (ICOS)-monoclonal antibody (ICOS-ImmunoPET), taking advantage of elevated ICOS in activated CAR-T cells and thereby tracking response and localization [170]. Multiple studies using novel PET isotopes incorporated with either MRI or CT are under study to improve diagnostic accuracy in GVHD, cellular therapy, and immune-based therapeutics.…”
Section: Imaging Of Immunotherapy and Cellular Therapymentioning
confidence: 99%